Assessment of biodegradable chelating agents in the phytoextraction of heavy metals from multi–metal contaminated soil. (June 2021) - Diarra, Ivan; Kotra, Krishna Kumar; Prasad, Surendra
Abstract: A pot incubation experiment under natural conditions was designed to investigate the effects of three biodegradable chelating agents, namely; the [S, S]-isomer of ethylenediamine disuccinate (EDDS), citric acid (CA), and tetrasodium N, N-Bis(carboxymethyl)-L-glutamate acid (GLDA), on two plant species ( Brassica juncea and Brassica rapa ) in terms of plant foliar growth, dry matter yield, and heavy metal (HM) accumulation. Both plant species exhibited diminished growth and symptoms of phytotoxicity under HM stress. The application of EDDS and CA affected plant foliar growth, biomass production, and led to the development of chlorotic lesions on leaves. EDDS and CA also decreased the shoot length by 38.5% and 45.2% in B. juncea, and 60.1% and 100% in B. rapa, respectively. In contrast, GLDA relieved HM stress by significantly increasing plant growth (P > 0.05) and was shown to be well tolerated (tolerance index [TI]; B. juncea  = 99% and B. rapa  = 123%). Among both plants, B. juncea displayed the ability to accumulate a wider range of HMs at higher concentrations. Amongst the three chelators, EDDS induced the highest bioconcentration (BCF) of Pb (2.45), Zn (2.68), and Cd (3.36) while CA achieved better results for Ni (4.01) and Cr (1.45). However, the current results showed that even with the application of chelating agents, HMs were predominantly accumulated in roots and translocation factor was generally <1. The findings of this investigation emphasize that chelate–assisted phytoextraction with Brassica spp. is highly limited in multi–metal settings, making it an unsuitable option for severely contaminated sites. Graphical abstract: Image 1 Highlights: Brassica spp. can tolerate and accumulate a wide range of heavy metals. Phytoextraction by Brassica spp. is limited in multi-contaminated soils. EDDS induces high metal bioconcentration compared to CA and GLDA. GLDA alleviates heavy metal stress in plants and enhances plant growth. Metals are predominantly accumulated in roots with poor translocation to shoot (<1).